2022
DOI: 10.3390/insects13050404
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Trends in Distribution and Seasonality of Medically Important Ticks in North America Using Online Crowdsourced Records from iNaturalist

Abstract: Recent increases in the incidence and geographic range of tick-borne diseases in North America are linked to the range expansion of medically important tick species, including Ixodes scapularis, Amblyomma americanum, and Amblyomma maculatum. Passive tick surveillance programs have been highly successful in collecting information on tick distribution, seasonality, host-biting activity, and pathogen infection prevalence. These have demonstrated the power of citizen or community science participation to collect c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Another possibility is that geckos are more likely to be observed over the warmer summer months when weather is more favourable for field work and/or tramping, which could increase the chances of detecting ectoparasites at these times. Seasonality in ectoparasite occurrence is common in other host–parasite systems and has been detected in another study using crowd‐sourced data (Cull, 2022).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Another possibility is that geckos are more likely to be observed over the warmer summer months when weather is more favourable for field work and/or tramping, which could increase the chances of detecting ectoparasites at these times. Seasonality in ectoparasite occurrence is common in other host–parasite systems and has been detected in another study using crowd‐sourced data (Cull, 2022).…”
Section: Discussionmentioning
confidence: 84%
“…Notably, 42% of observations (n = 104 total observations) contributed by one 'user' had mites detected in them, and the average latitude of their observations was 39.51° S (0.89 SD) which could explain the second peak of prevalence around 39° S-40° S. Thus, user variability -particularly for users that are highly active -could generate patterns in the data that do not necessarily reflect biological patterns. Other studies have found highly active users account for a large number of observations, generating a bias in observations around certain localities (Di Cecco et al, 2021;Dimson & Gillespie, 2023).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A. americanum is found primarily in the south, southeast and eastern coast of the US, with scattered observations in more northerly states of the upper midwest and northeast and the lower areas of Ontario [ 54 ]. It is important to realize that these observations primarily reflect recent tick surveillance data.…”
Section: Tick Infection Distribution and Rangementioning
confidence: 99%
“…Similar global databases updated by the research community as a whole (as opposed to a single team or project) exist in other branches of Life Science and are used not only as references and search engines for data points, but also as entire datasets in analyses of broad-scale patterns, acknowledging that all such databases are incomplete and unevenly sampled, but sufficiently broadly sampled to represent global patterns , e.g iNaturalist (conservation and ecology; www.inaturalist.org[e.g. [24][25][26]), Treebase (phylogenetics; www.treebase.org [e.g. 27,28]), Paleobiology Database (palaeontology; paleobiodb.org [e.g.…”
Section: Introductionmentioning
confidence: 99%